Organocatalytic stereoselective approach to the total synthesis of (-)-halosaline - Jha, Vishwajeet; Kumar, Pradeep (RSC Advances, 2014)
A practical and efficient organocatalytic approach to the synthesis of substituted piperidine alkaloids in high enantio- and diastereomeric excess was achieved using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and HWE olefination reaction of an aldehyde.